2012
DOI: 10.1371/journal.pone.0047461
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Profile of Long-Lived Drosophila melanogaster

Abstract: We investigated the age-related changes in the metabolic profile of male Drosophila melanogaster and compared the metabolic profile of flies selected for increased longevity to that of control flies of equal age. We found clear differences in metabolite composition between selection regimes and among age groups. Contrary to results found in a previous study of the transcriptome of these lines the metabolic profile did not show a younger pattern in longevity-selected (LS) flies than in same aged control (C) fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 57 publications
3
32
0
2
Order By: Relevance
“…16 In addition, metabolic profiling of longevity-selected Drosophila established clear differences in steady-state metabolite composition at all ages compared to age-matched controls. 17 This mirrors similar data in C. elegans 18 and mice. 19 Caloric restriction studies in Drosophila 20 and mice 19 provide another link between organismal metabolism and longevity, suggesting not only that caloric restriction causes increased lifespan, but that slowing the changes in the metabolome of flies with age conferred these systemic benefits.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…16 In addition, metabolic profiling of longevity-selected Drosophila established clear differences in steady-state metabolite composition at all ages compared to age-matched controls. 17 This mirrors similar data in C. elegans 18 and mice. 19 Caloric restriction studies in Drosophila 20 and mice 19 provide another link between organismal metabolism and longevity, suggesting not only that caloric restriction causes increased lifespan, but that slowing the changes in the metabolome of flies with age conferred these systemic benefits.…”
Section: Introductionsupporting
confidence: 81%
“…3(c) and 3(d)], consistent with data suggesting glucose accumulation in longevity selected flies. 17 In addition, we detected significantly increased levels of melezitose with age in VincHE flies [Fig. 3(e)].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Drosophila melanogaster has been cited as a particularly useful insect model for metabolomic studies (e.g. Chintapalli et al, 2013), and recent studies have identifi ed many interesting patterns of metabolome variation in this species: for example, variation across the sexes (Hoffmann et al, 2014) and with age (Sarup et al, 2012;Hoffmann et al, 2014), as well as metabolic plasticity to various environmental factors as adults (Overgaard et al, 2007;Colinet et al, 2012;Laye et al, 2015;Williams et al, 2015) and as larvae (Kostal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The abundances of individual metabolites change with age in several species, including worms [67,68], flies [35,69], mice [7072], and humans [57,73,74]. In the same vein, differences in abundances of individual metabolites have been associated with long life across multiple species, including work on long-lived mutant worms [75], longevity selected flies [76], calorie restricted and long-lived mutant mice [77], and long-lived human populations [7880]. Interestingly, fewer studies have attempted to find protein biomarkers of ageing or longevity, and those studies that have been carried out have found mixed results.…”
Section: Proteomics and Metabolomics As Ageing Biomarkersmentioning
confidence: 99%